(untitled) (Architecture Image Studies, 2026)
Road safety is a critical concern worldwide, directly influencing public health, economic stability, and overall quality of life. As the number of vehicles on the road continues to rise, the quality of infrastructure—roads, bridges, signage, and traffic control systems—plays a pivotal role in determining safety outcomes. This study investigates how age and gender influence road safety perceptions, behaviors, and experiences among 1,490 respondents in Iraq. Females constituted 56.5% of participants, with a majority (40.9%) aged 18–25, reflecting Iraq’s youthful demographics. Findings reveal significant age and gender disparities: middle-aged respondents (46–55 years) perceived roads as less safe than younger groups, contrasting with trends in high-income countries. Gender differences emerged, with females rating roads as safer (159 vs. 100 males) and males reporting more risky behaviors (e.g., phone use while driving: 22 males vs. 7 females). Seatbelt non-use was unexpectedly rare among males (0 cases vs. 36 females), suggesting cultural or reporting biases. Factor analysis identified three key components: (1) satisfaction with road safety infrastructure and efforts, (2) personal safety compliance (e.g., seatbelt use), and (3) a paradoxical link between high-risk perception and risky behaviors, possibly due to risk normalization. The study highlights the need for targeted interventions, such as awareness campaigns and stricter enforcement, to address these disparities and improve road safety in Iraq. It is vital for policymakers, municipal planners, and the public to understand the complex relationship between road safety and the quality of infrastructure to create a safer road environment and minimize the catastrophic impact of traffic-related accidents.